Spectroscopic studies, DFT calculation, electronic properties and antimicrobial studies on 2-(2-(naphthalene-2-yloxy)-1-phenylethylidene) hydrazine carboxamide. (2022) - Rajmohan, G.; Shanmugam, R.; Elangovan, A.; Ravindran, G.; Sangeetha, T.; Arivazhagan, G.
Abstract: We report the 2-(2-(naphthalene-2-yloxy)-1-phenylethylidene) hydrazinecarboxamide (NAPCAR ) compound has been synthesized from 2-(naphthalene-2-yloxy)-1-phenylethanone (2-NAPETH ), the parent compound. The characterization of both the parent and product has been done using FT-IR, 1 H NMR and 13 C NMR spectroscopic and theoretical studies. Solid double bonds have been identified near some of the aromatic ring carbons instead of the partial double bond in both the parent and the title compounds. The Highest Occupied Molecular Orbital (HOMO) is found to be concentrated mainly on the naphthyl ring in both 2- NAPETH and NAPCAR. However, major portion of Lowest Unoccupied Molecular Orbital (LUMO) has been found to be spread over the naphthyl ring of NAPCAR unlike the2- NAPETH which has LUMO on the benzyl ring. The electrostatic potential surface (ESP) shows that both the 2- NAPETH and NAPCAR have nucleophilic site only. This NAPCAR is found to be against the pathogenic bacteria and fungi indicating that this compound may be considered as a candidate to be used in the development of new drugs capable of treating microbial infections.